1993
DOI: 10.3109/09537109309013216
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Association of the Platelet Fc-receptor with the Glycoprotein IIb-IIIa Complex

Abstract: In this study, we have examined whether the platelet Fc-receptor, FcγRII (CD32), is associated with either of the two major platelet membrane glycoproteins, the GPIb-IX complex and the GPIIb-IIIa complex. Monoclonal and polyclonal anti-GPIb-IX complex antibodies inhibited to only a moderate degree (< 40%) the binding of the anti-FcγRII monoclonal antibody, IV.3, to platelets. In contrast, 6 of 12 anti-GPIIb-IIIa monoclonal antibodies and a polyclonal, affinity-purified rabbit anti-GPIIb-IIIa antibody strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…While there is no evidence for a direct physical association between αIIbβ3 and FcγRIIa, and they cannot be coimmunoprecipitated from detergent lysates (P.J. Newman and C. Gao, unpublished observations), they do appear to be topographically close to each other on the platelet surface, as evidenced by the finding that several αIIbβ3-specific mAbs, when prebound, are able to sterically block the binding of the anti-FcγRIIa mAb IV.3 (67,68). Because αIIbβ3 complexes are present at relatively high density on the platelet surface (~40,000-80,000 per platelet; refs.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no evidence for a direct physical association between αIIbβ3 and FcγRIIa, and they cannot be coimmunoprecipitated from detergent lysates (P.J. Newman and C. Gao, unpublished observations), they do appear to be topographically close to each other on the platelet surface, as evidenced by the finding that several αIIbβ3-specific mAbs, when prebound, are able to sterically block the binding of the anti-FcγRIIa mAb IV.3 (67,68). Because αIIbβ3 complexes are present at relatively high density on the platelet surface (~40,000-80,000 per platelet; refs.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal Antibodies-Monoclonal antibodies to GPIb-IX (AK2), ␣2␤1 (AK7), and CD36 (IE8) have been described previously (33,34); anti-␣v␤3 (AP-3) and anti-CD4 (OKT-4) were obtained from the American Type Culture Collection; and the anti-integrin-associated protein monoclonal antibody B6H12 (26) was a kind gift of Dr. Eric J. Brown (Washington University School of Medicine, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, although the induction of aggregation by mAbs still required Fc-FcgRII interaction, the triggering of FcgRII signal alone by crosslinked Fab 2 fragments of IV.3 mAb gave only a weak response, whereas the aggregation response to LeoA1 and SYB-1 was much stronger and more persistent. Since FcgRII expression is increased following platelet activation (from a range of 1000-2000 receptors/platelet on resting platelets to values >2000 receptors/platelet on activated cells (McCrae et al, 1990)), any change in antigen density as a result of platelet degranulation (Berndt et al, 1993) is very unlikely to account for the observed weak response of degranulated platelets to FcgRII engagement as compared with their much stronger and apparently equal responses to both SYB-1 and LeoA1. Resting platelets express 1200 and 35 000-65 000 molecules/cell of PTA-1 (Scott et al, 1989) and CD9 (Hato et al, 1988) respectively.…”
Section: Discussionmentioning
confidence: 99%